Optimizing the solvent mixture for extracting phenolic compounds with antioxidant and phytotoxicity activity from Myrcia fallax leaves using the I-optimal design (Research, Society and Development, 2025)
The objective of this study was, through an I-optimal design, to enhance the extraction of total phenolic content (TPC) and total flavonoid compounds (TFC) from Myrcia fallax (A. Rich) DC leaves from a mixture of three solvents of Ethanol, Methanol, and water (maximum 50%) to get the best yield, antioxidant and phytotoxic results. Methanol provided higher percentage yields of extraction, while for Total Phenolic Content (TPC) and Total Flavonoid Content (TFC), better values were given to methanol-water. Also, pure ethanol had better results regarding antioxidant activity using DPPH and the ABTS methods. For phytotoxicity activity evaluation, extracts from methanol-water were indicated due to their ability to inhibit radicle length and stimulate hypocotyl growth compared to the control. Then, the I-optimal design allowed us to correlate the Myrcia fallax extracts with their biological activities from solvent-different polarity mixtures.